Employee benefits: a qualitative research study on the perceptions of HR-professionals with a strategic point of view on the use of flexibility, communication and employee involvement - Geert, Jessica Alfonsine G Van (2019)
In today’s highly competitive environment, the goal of organizations is to recruit, retain and stimulate employees to give high quality performance, which may be achieved by a welldeveloped renumeration system and a wide range benefits. As flexibility is an increasing important aspect within the business environment, we notice the importance of flexibility within benefits which leads that different choices of benefits are increasing and makes the field of benefit communications has becoming more complex. It was the aim of this project to broaden understanding on flexibility within the employee benefits with a strategic point of view, the communication processes and how high the employee involvement is. This paper reports results from a qualitative research with semistructured interviews with HR professionals to examine their perceptions on employee benefit communication. The interview addressed the strategic approach to benefits, the prevalence of particular communication channels, the perceived effectiveness of those channels, the importance of employee benefit communication within the HR and company strategy and the involvement of employees. Results indicate that organizations are following from strategic perspective more institutionalized approaches rather than make the choice for following a differentiation strategic on their competitors. Employee benefit communication is still not high on the agenda of HR but still some organizations are already aware that by introducing flexibility within employee benefits, the communication process is becoming more and more important.